Religion and enlightenment in Catherinian Russia the teachings of Metropolitan Platon - Wirtschafter, Elise Kimerling (NIU Series in Slavic, East European, and Eurasian Studies, 2013)
Intro -- Contents -- Acknowledgments -- Note on Dating and Biblical Citations -- Introduction -- 1-The Meaning of Enlightenment -- 2-Christian Enlightenment and Enlightenment Learning -- 3-Divine Providence and Human History -- 4-Free Will and the Human Person -- Conclusion-Toward a Definition of the Russian Enlightenment -- Appendix-1Chronology of Metropolitan Platon's Career -- Appendix 2-Metropolitan Platon's Subscribers -- Notes -- Bibliography -- Index.